Prolonged Gadget Use May Delay Language Development in Young Children: Penggunaan Gadget Terlalu Lama Dapat Menunda Perkembangan Bahasa pada Anak - Fida Putri Nurrahma Aliany; Hesty Widowati (Academia Open, 2024)
This study examines the relationship between gadget use duration and language and speech development in toddlers aged 3-5 years in Ketimang Village, Wonoayu. Using a cross-sectional analytic observational method, data were collected from 30 mothers through questionnaires on gadget use and developmental screening. The results indicated that most children using gadgets for over an hour showed doubtful language and speech development, but no significant relationship was found. The findings highlight the need for cautious gadget use among young children to prevent potential developmental delays. Ethical considerations, including anonymity and informed consent, were strictly observed. Highlight: Participants: 30 mothers with 3-5-year-old toddlers in Ketimang Village. Finding: Gadget use over one hour showed doubtful language development. Ethics: Ensured anonymity, confidentiality, and informed consent. Keyword: Gadget use, language development, speech development, toddlers, cross-sectional study